Histological assessment of granulomas in natural and experimental Schistosoma mansoni infections using whole slide imaging - Amaral, Kátia B.; Silva, Thiago P.; Dias, Felipe F.; Malta, Kássia K.; Rosa, Florence M.; Costa-Neto, Sócrates F.; Gentile, Rosana; Melo, Rossana C. N. (PLOS ONE, 2017)
The pathology of schistosomiasis mansoni, a neglected tropical disease of great clinical and socioeconomic importance, results from the parasite eggs that become trapped in host tissues, particularly in the liver and intestines. Continuous antigenic stimulation from these eggs leads to recruitment of inflammatory cells to the sites of infection with formation of periovular granulomas. These complex structures have variable size and composition and are the most striking histopathological feature of schistosomiasis mansoni. However, evaluation of granulomas by conventional microscopy methods is time-consuming and limited, especially in large-scale studies. Here, we used high resolution Whole Slide Imaging (WSI), which allows fast scanning of entire histological slides, and multiple morphometric evaluations, to assess the granulomatous response elicited in target organs (liver, small and large intestines) of two models of schistosomiasis mansoni. One of the advantages of WSI, also termed virtual microscopy, is that it generates images that simultaneously offer high resolution and a wide field of observation. By using a model of natural (Nectomys squamipes, a wild reservoir captured from endemic areas in Brazil) and experimental (Swiss mouse) infection with Schistosoma mansoni, we provided the first detailed WSI characterization of granulomas and other pathological aspects. WSI and quantitative analyses enabled a fast and reliable assessment of the number, evolutional types, frequency and areas of granulomas and inflammatory infiltrates and revealed that target organs are differentially impacted by inflammatory responses in the natural and experimental infections. Remarkably, high-resolution analysis of individual eosinophils, key cells elicited by this helminthic infection, showed a great difference in eosinophil numbers between the two infections. Moreover, features such as the intestinal egg path and confluent granulomas were uncovered. Thus, WSI may be a suitable tool for detailed and precise histological analysis of granulomas and other pathological aspects for clinical and research studies of schistosomiasis.